10 EFFECT OF SUBSPECIALTIES OF GASTRO-INTESTINAL SURGERIES ON PATIENT'S OUTCOMES. (17th September 2021) - Ezz, Reda
Abstract: : Subspecialty policy is increasing all over the world aiming to improve the results of heavy esophageal surgeries. Our aim is to define the impact of having surgical specialized esophageal unit on the volume of patients and the results. Methods: We reviewed all esophageal cases managed in our esophageal specialized department (from May 2016 to May 2019 Group A) and we compared the results to previous 3 years (from May 2013 to May 2016 Group B) and to the international results. There was 394 cases in group A compared to 104 cases in group B. Results: For Gastro esophageal reflux disease (GERD), 180 operations were performed in group a (45.7%) compared to 61 cases in group B (68.7%). Forty two (10.7%) modified Heller's cardiomyotomy (Open and laparoscopic) for achalasia were performed in group A compared to 17 cases (16.3%) in group B. Surgeries for malignant lesions were performed for 122 cases (30.9%) in group A compared to 13 cases (12.5%) in group B. Other Esophageal operations were also done for 50 cases (12.7%) in group A compared to 13 cases (12.5%) in group B. Morbidities and mortalities are reported and compared to the international results. Conclusion: Our results in group A are comparable to Hospital mortality rates for patients in medium-volume centers (7.5%). Also we approach the International results for morbidities of benign esophageal disease (5.7–12.7%) for fundoplication. Having a specialized esophageal unit resulted in increase of the volume of patients and improvement of the results.